Biological significance of glutathione S-transferases in human sperm cells - Roman V Fafula; Nataliya M Paranyak; Anna S Besedina; Dmytro Z Vorobets; Ulyana P Iefremova; Olena K Onufrovych; Zinoviy D Vorobets (Wolters Kluwer Medknow Publications, 2019)
Background: Oxidative stress is considered as one of the causes of male subfertility or infertility. Among antioxidant enzymes, the crucial role belongs to glutathione S-transferases (GSTs). Data on the biological role of GSTs in the defense mechanisms of sperm cells in fertile and infertile men are limited. Aim: The aim of this study was to demonstrate the functional role of GSTs in sperm cells on the model of H2O2-induced stress on human ejaculated spermatozoa obtained from both normospermic and pathospermic patients. Subjects and Methods: We used a H2O2-induced stress on human ejaculated spermatozoa obtained from both normospermic and pathospermic patients. Results: Here, we report the effect of GST inhibitor ethacrynic acid on sperm motility and viability. Pharmacological inhibition of sperm GSTs activity leads to spermal membrane damage and rejected in the loss of motility and decrease of viability. For similar treatment conditions, thiobarbituric acid reactive substance (TBARS) levels increased significantly leading to decrease in sperm motility and viability. It is suggested that these functional impairments are related to the intensification of lipid peroxidation as expressed by TBARS levels in spermal membranes after GST inhibitor treatment. Conclusion: This study provides evidence that sperm GSTs are important in the defense mechanism against oxidative stress. Evaluation of GSTs activity in sperm cells of infertile men can be helpful in fertility assessment and for the evaluation of treatment by antioxidants.